Strategi Komunikasi Pemasaran Terpadu (IMC) Discovery Kartika Plaza Hotel Bali dalam Membangun Citra Perusahaan - Nugroho Setiawan, Thalia Patricia; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2023)
Discovery Kartika Plaza Hotel is the oldest 5-star hotel in Bali's Kuta Beach area. Despite the pandemic, it still attracts tourists because of its corporate image of being a